(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the methodological foundations of solving problems related to the laws of electrolysis in chemistry teaching. The main purpose of the article is to explain Faraday’s laws through practical problem-solving and to develop students’ ability to quantitatively analyze chemical processes and improve logical thinking skills. During the research, step-by-step algorithms for solving problems and their impact on students’ level of understanding were studied. The results show that a systematic and algorithmic approach is the most effective tool for connecting theoretical knowledge with practice.